Fabrication and Characterization of Pineapple Leaf Fiber (PALF) as Candidate of Composite Reinforcing Material - Ratulangi, Wulan Ratia; Widyan, Rosnalia; Suhada, Adriyan; Dani, Rahmad (IKIP Mataram, 2025)
Pineapple leaf is a waste product of pineapple cultivation which may leads to environmental issues. Pineapple leaf fibre (PALF) is an important natural fibre with high cellulose content that exhibits high mechanical properties which is high specific strength and stiffness which may vary for each cultivar. Besides, isolation of cellulose from lignocellulosic fibre become more crucial. In this study, isolation of cellulose were undergo by alkaline treatment In that order, concentration of NaOH 0.5% at 121oC for 60 min and bleaching teatment using NaClO 10% at 121oC for 30. The PALF and treated fiber were characterized using Tensilon, Scanning Electron Microscopy, Fourier Transmission Infrared Spectroscopy. Based on results, 5% NaOH (60 min) and bleaching process by using 10% NaClO (30 min) in autoclave succeed to remove pektin, lignin, and unwanted components. The surface morphology showed high surface area, however still remaining small amaount of pektin and lignin was confirmed from FTIR and SEM images.